Dataset for the near-complete hybrid genome assembly of Citrobacter werkmanii UPMLSS01 isolated from Borneo river and insights into its native antibiotic resistance repertoireNCBI - Sui Sien Leong; Han Ming Gan (Data in Brief)
The near-complete genome sequence of a Citrobacter werkmanii UPMLSS01, isolated from the Kemena River in Bintulu, Sarawak, Malaysia, is presented. Remarkably, this bacterium exhibited resistance to beta-lactam despite no prior exposure, suggesting an innate resistance mechanism in an environment increasingly impacted by anthropogenic pressures. Genome sequencing was performed using both Illumina (2 × 150 bp paired-end) and Oxford Nanopore technologies, yielding a high-quality de novo assembly with a total length of 4994,936 base pairs, a GC content of 52 %, and an N50 of 3.5 Mb. The assembly comprises three contigs, none of which were identified as plasmid or mobile elements. Genomic analysis revealed that the strain belongs to sequence type 948, while also harboring the blaCMY gene presumably responsible for the beta-lactam resistance. Notably, this is the first genome of Citrobacter werkmanii reported from Borneo, Malaysia, underscoring a significant milestone that provides a robust baseline for future phylogenomic studies and molecular resistance profiling in both environmental and clinical settings.